Protection of human rights and the environment: links and approaches - Abdulkadir, A.B.; Mustafa, Maizatun; Ansari, Abdul Haseeb (AENSI Publications, 2012)
Abstract: Environmental degradations have adverse consequences, both short-term and long-term on the efficacious enjoyment of environmental human rights. Though these consequences are the results of the errant use and abuse of the environment resources by the affluent people and rich states around the globe, and their engagement with such activities that are not environmentally friendly, the most susceptible and sufferers are less privileged and indigent population of the developing and least developed countries. The best example of it is the phenomenon of global warming and its impact on countries across the world. Global warming, which is causing adverse weather conditions as a result of excessive emission of greenhouse gases mostly by developed countries, has resulted in unusual whether conditions in developing and least developed countries. This has led to a sizable number of internally displaced people who are left in vulnerable conditions in such countries since they are practically less resourceful. In view of this, international cooperation for conservation of the environment, resuscitation of its damage based on transfer of technology, transfer of financial resources and capacity building of developing and least developed countries become a sine qua non for ensuring environmental human rights and other related rights to every individual of the world. The notion that environmental degradation affects the enjoyment of environmental rights and fundamental human rights has gone beyond a mere jurisprudential debate of a state and has become a matter of global concern. It has been acknowledged over the years that protection of human rights and environmental protection are so inextricably related that they are co-extensive and co-existent. Thus, attempt to protect the environment will also, in turn, assist in the protection of certain fundamental human rights. This proposition has been a subject matter of widespread debate. This paper, therefore, sheds some light on various issues that prove that the two subject matters, i.e. certain fundamental human rights and conservation of the environment, are interrelated. This underscores the need for both to be taken into consideration and incorporated into all development projects and activities, which might cause adverse impact on the environment and/or human, animal and plant life or health. Towards achieving this, there is a need for preventive measures, e.g. comprehensive environmental impact assessments (EIAs) and social impact assessments (SIAs) with enough and meaningful public participation, environmental audit from time to time, and punitive measures, e.g. imposing penalty and fine, imprisonment, compensation having enough deterrence on the perpetrators and others, a competent legal regime and enforcement mechanisms, administrative and judicial. Due to limited space the paper will not discuss these imperatives in detail. Key words: Environment, human rights, development.